KAJIAN FONEMIK DALAM LIRIK LAGU “BETELGEUSE” KARYA YUURI - Damaranti, Puspita; Siagian, Irwan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze and find out whether different words even though only one letter can distinguish meanings such as in the phonemic level found in the song Betelgeuse and the lyrics are written by the singer himself, namely Yuuri. The method used is descriptive analysis using a qualitative approach. According to Sugiyono (2015: 207), descriptive qualitative analysis technique is data analysis by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public. The bt hpsource of the data obtained in this study is the lyrics of a song entitled Betelgeuse by Yuuri which is sourced from a digital search platform, namely Google. The data collection technique used is reading and taking notes. The results showed that in the Betelgeuse song, even though the writing was similar and differed by one letter and the pronunciation was also very similar, it still had a different meaning and could be said to be a phonemic phoneme. The results of this study are expected to be the basis of research that will be taken by other researchers.